CGIAR Road from COP29 to COP30 Webinar Series #3 : The Global Goal on Adaptation (GGA) - CGIAR Science Program on Climate Action (2025)
The CGIAR Road from COP29 to COP30 Webinar Series is bringing together experts to unpack the key negotiation tracks shaping climate finance and adaptation in the lead-up to COP30. Our last session explored the New Collective Quantified Goal (NCQG)—a landmark climate finance commitment of $1.3 trillion annually by 2035—and raised important questions on whether the pledged finance will truly reach the sectors and communities that need it most. If you missed it, catch up on the recap here.